Relasi Manusia dan Lingkungan dalam Semasa Kecil di Kampung Karya Muhammad Radjab: Ekologi Sastra - Nurul Azisyah Amini Amiruddin; Andi Karman; Aslan Aslan; Usman Usman (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
Literary studies that highlight the relationship between humans and the environment are essential for understanding how ecological values are represented and passed down through literary texts. This study aims to analyze the representation of the relationship between humans and the environment in *Semasa Kecil di Kampung* through the lens of literary ecology. The study employs a qualitative approach using content analysis of the text, utilizing the ecocritical framework proposed by Glotfelty, Garrard, and Buell, which views nature as an active element in the construction of meaning. The results of the study indicate that the relationship between humans and the environment is represented through two main categories: cosmic ecology and spatial ecology. Cosmic ecology portrays human life as part of the universe’s cycle, encompassing birth, death, and the interpretation of natural phenomena as a cosmological order imbued with moral and spiritual significance. Meanwhile, spatial ecology portrays the natural environment as a place, dwelling, and wilderness that shapes the characters’ identities, social structures, and inner consciousness through spaces such as valleys, rivers, forests, and hills. This study concludes that the work represents nature not as a passive backdrop, but as an active ecological element that reflects the local wisdom of the Minangkabau people in building a harmonious relationship between humans and the environment.